PUBLIC CONTROL-A SIGN OF A DEMOCRATIC STATE - Umarov Murodjon Mamatkarim ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article describes the nature of public control and its importance in the formation of a democratic state, the joint development of civil society and public control, as well as the entities conducting public control and forms of public control.